Intervensi Keperawatan untuk Menurunkan Kecemasan Pasien Dengan Acute Myocardial Infarction - Tri Wahyuni Ismoyowati; Bernadeta Kristanti; Brilian Yudistira Nugraha; Theresia Rini Yuwanti (FORIKES, 2020)
Acute Myocardial Infarction (AMI) is also known as a heart attack, coronary occlusion, or just coronary, which is a life-threatening condition characterized by the formation of local necrotic areas within the myocardium. One that is very influential on the psychological state of patients with heart problems that will be able to change the coping patterns of patients in dealing with the disease and live their lives is the emergence of anxiety. This paper is a literature review / literature review from several data bases namely Google Schoolar, ScienceDirect, NCBI and PubMed. Search articles are limited from 2010 to 2020. The author uses the keywords